Seleção de genótipos superiores em coleções ex situ de Camu-camu [Myrciaria dubia (Kunth) McVaugh] na Amazônia peruana - Panduro, Mario Herman Pinedo (2017)
The aimed of this study selection high genotypes ex situ collections of camu-camuzeiro [Myrciaria dubia (Kunth) McVaugh] from the Peruvian Amazon. Thus, camu-camu individuals were evaluated and selected promising genotypes in terms of productivity, precocity, fruit weight, vitamin C and tolerance to fruit weevil. They were analyzed, without delineation, with entirely randomized design and in randomized blocks, with variable number of repetitions (4 to 10). The SELEGEN-Reml/Blup statistical program was applied to analyze the harvest repeatability (3 to 10 years). Parental samples were selected with high productivity, fruit weight and ascorbic acid content in four sets of collections and genetic tests. After 10 years of evaluation of fruit yield in 115 families from five basins, the repetitiveness index was r = 0.322 and individuals P0511, NN0202, NN0907, NY0805 and NY0413 were selected. For the average fruit weight we calculated r = 0.736, and selected individuals Ct0107, PC0511, PC0913, PC0602 and TH0215. In the evaluation of 37 clones for fruit yield a r = 0.117 was obtained where clones 69, 48, 58, 50 and 61 were selected. For the average fruit weight, the r reached 0.69 with the selection of the clones 44, 13, 26, 23 and 69. Regarding the ascorbic acid content the clones 48, 32 and 35 occupied the first places with more than 2000 mg/100 g. In the search for genes for precocity, 108 pre-selected progenies were evaluated as early and after 3 harvest an rm = 0.15 was obtained for fruit yield with the selection of plants: 98-1, 206-6, 98-12, 229-3 and 44-12. For their tolerance to fruit weevil, individuals 51-2, 164-3, 220-10, 10-12 and 98-1 were selected. When evaluating 43 advanced progenies for fruit yield, highlighted the individuals: TT0725-9, TT0812-5, TT0725-4, Pc0504-5 and BMC1-8. Natural recombinant individual for fruit yield/weight is TT0725-4 and the plant 64-8 for yield/fruit weight/ascorbic acid. The descriptors of greater genetic control (r ≥0.30) resulted: average fruit weight, brix degrees, plant height, number of basal branches and petiole length. In addition to the criteria of heritability and correlation, the similarity criterion is proposed. It is considered that the variable "plant height" is the most adequate to predict the yield of fruit. The present results reinforce the importance of the long term investigation of superior camu-camu genotypes.